Autophagic bias in the striatum. Issue 6 (2nd June 2020) - Pigulevskiy, Irena; Lieberman, Ori J.; Sulzer, David
ABSTRACT: Macroautophagy/autophagy is implicated in the maintenance of normal neuronal activity through the regulation of synaptic function and plasticity. However, differences in autophagic degradation within different classes of neurons have not been examined. We have recently demonstrated that autophagy plays very different roles in the two closely related principal neurons of the striatum – the spiny projection neurons of the direct (dSPN) and indirect (iSPN) pathways. Behavioral and electrophysiological experiments revealed that the absence of autophagy in either of these SPN pathways produces unique effects on motor learning, dendritic length, and intrinsic excitability. Specifically, autophagy is required for the normal development of synaptic inputs onto dSPNs, while being required for intrinsic excitability in iSPNs. In iSPNs, this occurs through the regulation of the activity of the KCNJ/Kir2 ion channel, and provides a first demonstration of autophagic control of neuronal intrinsic excitability. Abbreviations: ASD: autism spectrum disorders; dSPNs: direct pathway spiny projection neurons; iSPNs: indirect pathway spiny projection neurons; Kir2: inwardly rectifying potassium channel 2.